Utilization of Drones Technology in Infrastructure Inspection and Maintenance - Morse Kathryn; Wang Joshua; Elladdadi Mark (Journal of Moeslim Research Technik, 2024)
The utilization of drones technology in infrastructure inspection and maintenance has become an important topic in civil engineering and infrastructure management studies. Adequate infrastructure supports the social and economic progress of a country, but requires regular maintenance to ensure its reliability. This research aims to investigate the effectiveness of utilizing drone technology in performing infrastructure inspection and maintenance, and to evaluate its impact on the efficiency and accuracy of the process. The research method used was a literature study and analysis of data from previous studies relevant to this topic. In addition, the research also involved primary data collection through interviews with experts in the field of drones and infrastructure technology. The results show that the utilization of drones technology can significantly improve the efficiency and accuracy in conducting infrastructure inspection and maintenance. Drones are able to reach areas that are difficult to reach manually and provide detailed and real-time data. The utilization of drone technology is a very potential solution in improving efficiency and accuracy in infrastructure inspection and maintenance. By utilizing drones, the process can be done more quickly, cheaply, and safely, so that it can support sustainable infrastructure development.